Critical issues in existing RC deck stiffened arch bridges under seismic actions. (1st December 2022) - Crisci, Giovanni; Ceroni, Francesca; Lignola, Gian Piero; Prota, Andrea
Highlights: Technical background about RC Deck Arch Bridges in Italy - design principles largely adopted in the past are summarized; Numerical studies to generate simulated samples of RC Deck Arch Bridges; Procedure for assessment of seismic vulnerability for RC Deck Arch Bridges and derivation of preliminary fragility functions at Ultimate Limit State. Abstract: Existing Reinforced Concrete arch bridges represent still today an important part of transportation network. The peculiarities of such bridges make particularly complex the assessment of their behaviour under both static and dynamic actions and, therefore, their safety. This work concentrates on a specific arch bridge typology known as the "Maillart –Type Arch Bridges" or "Deck-Stiffened Arch Bridges", characterized by a very stiff deck beam and a slender and wide vault. As well as for the RC structures designed during 50s of the last century, where some important details for concrete elements were not considered, RC Deck-Stiffened Arch Bridges could be subjected to similar structural deficiencies. Moreover, the current loading conditions provide actions that were not considered in the original design or have changed over the time, such as the seismic actions or the moving loads due to the vehicular traffic. For the evaluation of the main critical issues related to the current performance of the "Maillart–Type Arch Bridges", this study, starting from a "simulated design" according to the design rules and the mandatory codes in force at the construction time, defines a large building inventory of simulated bridges (3000 samples) characterized by different values of the most significant geometrical parameters. Firstly, each bridge of the inventory is modelled and studied by means of a linear Response Spectrum Analysis (RSA) implemented in the software SAP2000. The large number of structural analyses allowed to investigate the seismic behaviour of such a bridge typology, assess and localize the most frequent failure modes. The results of the RSA allowed developing preliminary fragility functions at the Ultimate Limit State, based on shear or flexural failure of single elements of the bridges. Lastly, Non-Linear Time History Analyses (NLTHA) were carried out on two representative case studies extracted from the simulated inventory and the results were examined in terms of fragility curves obtained according to the Cloud methodology for four Damage States. Despite the different approaches (RSA on large scale and NLTHA on two prototypes), a comparison of the fragility curves for equivalent Damage States was also proposed and a good agreement was found. These fragility curves are a first step for the assessment of the seismic vulnerability of "Maillart–Type Arch Bridges" and can be useful for planning seismic risk mitigation interventions for such a bridge typology.